2020
DOI: 10.1051/0004-6361/201937318
|View full text |Cite
|
Sign up to set email alerts
|

A detailed non-LTE analysis of LB-1: Revised parameters and surface abundances

Abstract: Context. LB-1 has recently been proposed to be a binary system at 4 kpc consisting of a B-type star of 8 M and a massive stellar black hole (BH) of 70 M . This finding challenges our current theories of massive star evolution and formation of BHs at solar metallicity. Aims. Our objective is to derive the effective temperature, surface gravity and chemical composition of the B-type component in order to determine its nature and evolutionary status and, indirectly, to constrain the mass of the BH. Methods. We us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 33 publications
5
53
0
1
Order By: Relevance
“…They suggested that the unseen secondary component is a neutron star or a faint mainsequence star and that the primary star is a stripped helium star that lost its H-rich envelope due to a past binary masstransfer event. This claim was based on anomalous abundances derived for the star, consistent with processed material from the CNO cycle (enriched N, depleted C and O), also confirmed by Simón-Díaz et al (2020). A notable peculiarity that was consistently reported in the aforementioned studies is the sub-solar abundance derived for several heavy elements such as Mg, Si, and Fe, which are not expected to change throughout the evolution of the star.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…They suggested that the unseen secondary component is a neutron star or a faint mainsequence star and that the primary star is a stripped helium star that lost its H-rich envelope due to a past binary masstransfer event. This claim was based on anomalous abundances derived for the star, consistent with processed material from the CNO cycle (enriched N, depleted C and O), also confirmed by Simón-Díaz et al (2020). A notable peculiarity that was consistently reported in the aforementioned studies is the sub-solar abundance derived for several heavy elements such as Mg, Si, and Fe, which are not expected to change throughout the evolution of the star.…”
Section: Introductionsupporting
confidence: 74%
“…Despite being fainter in the visual, the Be secondary is the more luminous component due to its higher temperature. We note that the comparable light contribution of the two components provides a natural explanation for the lack of evidence of binary motion in the Gaia astrometry (see Simón-Díaz et al 2020).…”
Section: B2 the Be-type Secondarymentioning
confidence: 75%
See 1 more Smart Citation
“…El-Badry & Quataert (2020a) and Abdul-Masih et al (2020) showed that the anti-phase signature of Hα cannot be readily interpreted as Doppler motion without considering the impact of potential Hα absorption of the B-type component. Simón-Díaz et al (2020) and Irrgang et al (2020) performed spectroscopic studies of the primary and found evidence for processed CNO material in its atmosphere, leading Irrgang et al (2020) to suggest that it is a low-mass stripped helium star. Subsequently, Shenar et al (2020) utilised spectral disentangling to show that the secondary in LB-1 is not a BH, but a classical Be star -a rapidly rotating B-type star with a decretion disc (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…这对经典的恒星演化理论提出了挑战. 该重要成果发 表在Nature上 [26] , 论文发表后引起了众多国际团队的 高度关注, 掀起了一场激烈的学术辩论 [27][28][29][30][31][32] . 对该结 果的主要质疑有两处: 即其氢元素的发射线可能并非 来自于随光学不可见天体运动的吸积盘, 而是来自于 环绕该双星系统的外部气体盘 [27,29] ; 光学可见的那颗 恒星可能并非B型星, 而是颗外壳层被剥离了的氦 星 [30] .…”
Section: 中国科学院国家天文台刘继峰、张昊彤及其团队 利用Lamost对kepler K2-0天区约3000颗恒星历时unclassified